“TUNTUTLAH ILMU DI NEGERI SAKURA”: Kuliah di Jepang dalam Persepsi Muslim Indonesia Alumni Jepang - Edy Hariyadi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
This article discusses the alumni of Japan Indonesian Muslimviewpoints in connection with their study experiences in Japan. Theirmotivations to study in Japan are opportunity available, the ease ofgetting a scholarship, boost the positive image of Japanese from theirparents, positive impression on Japan from their senior, interest inJapanese culture and technology advances, interest in English-languageclasses and programs. The constraints they face while studying in Japanis divided into academic and non-academic issues. Academic problemsare: different fields of study with academic tutors, language andcommunication problems, the problem of interaction with academiccounselors. Non-academic problems did not largerly happen becausethey did not experience financial problems, obtaining economicalaccommodation for academic tutors help, having special facilities forforeign students, can overcome the problem by cooking own food, buyfood at the halal food store or order via the internet, able to adapt todifferent weather and climate, and social support from the communityand the government of Japan that helps international students so thatthey feel comfortable studying in Japan.Keywords: Muslim, Indonesia, study, Japan